Student engagement as a mediator of learning outcomes in vocational education - Nurmaidia Rahmi; Elvi Rahmi (Journal of Educational and Learning Studies, 2026)
This study examined the effects of self-regulated learning and social capital on learning outcomes through student engagement as a mediating variable among vocational high school students. A quantitative explanatory survey was conducted with 371 students selected using proportional stratified random sampling. Data were collected through validated questionnaires and academic records and analyzed using multiple regression, path analysis, and the Sobel test. Self-regulated learning and social capital significantly influenced student engagement and learning outcomes (p < 0.001). Student engagement also significantly predicted learning outcomes (β = 0.303, p < 0.001) and partially mediated the effects of self-regulated learning and social capital. The proposed model explained 88.7% of the variance in learning outcomes (R² = 0.887). Strengthening self-regulated learning, social capital, and student engagement can effectively improve vocational students’ academic achievement and support evidence-based educational practices.